Fault lines after the Cold War: the vertical expansion of the concept of security, securitization and human security - Gama, Carlos Frederico Pereira da Silva (Monções: Revista de Relações Internacionais da UFGD, 2014)
The paper approaches the “vertical expansion of the concept of security” reconstructing the debate on the concept of security within the discipline of International Relations after the Cold War. Considering that security is an “essentially contested concept”, it offers a handful of comparisons between different conceptions, which provide different accounts of “broadening” security. Barry Buzan’s Securitization approach was the first to engage seriously the challenges of “broadening” security in IR. For its merits, however, Buzan’s communitarian ontology poses a problem to “broadening” security, as it reiterates the state as the gatekeeper of protection and as the authoritative site for defining existential threats. In this sense, in spite of all its overriding ambiguity, Human Security provides a better alternative for the “vertical expansion of the concept of security” than securitization. The paper, therefore, considers the respective contributions of securitization and human security to the debate on the vertical expansion of security under the light of the relationship between states and human beings.